NURTURING RESPONSIBILITY FOR THE YOUTH - Apriliaswati, Rahayu (Jurnal Pendidikan Sosiologi dan Humaniora, 2012)
One of the most important character traits that must be developed for the youth is responsibility. Responsibility is marked by how well people make choices in life and how people deal with the results.Responsible people purposefully choose their attitudes, words and actions, and accept responsibility for the consequences of these choices. Responsibility is not obtained from born. It needs a complex virtue, requiring much time, patience and practice to acquire. To teach teens responsibility, parents must focus on two dimensions of being responsible, which are thinking critically about a situation and making decisions about a situation. Both are skill sets that can greatly enhance teen self responsibility and also responsibility to the family and to society. This article is the literature review on how to teach responsibilities to the youth particularly teenagers